SOFTWARE SOLUTIONS FOR EFFICIENT FINANCIAL MANAGEMENT AND BUSINESS METRICS TRACKING - ХРИСТОВА, А. Р.; ЗОСІМОВ, В. В.; БУЛГАКОВА, О. С. (Technologies and Engineering, 2023)
Purpose. This paper presents the development of a software system for business metrics tracking. The purpose of this research is to provide business owners with a tool to keep track of their business metrics, allowing them to make data-driven decisions. Methodology. The methodology of this research includes an analysis of the problem area, identification of key business metrics, and examination of existing software solutions. Findings. This research reveal the importance of defining key business metrics for marketing, business modeling, financial planning, and other aspects. Analysis of existing software solutions identified their advantages and disadvantages, which helped to define the requirements for the software system. The software system was designed to provide the user with the ability to track and manage business metrics, collaborate with partners, and work remotely. Originality. This research lies in the development of a software system that provides clear instructions for use, data security, and online support. The practical value of the software system is that it provides a user-friendly interface for tracking business metrics, making data-driven decisions, and improving business performance. Practical value. This research provides a comprehensive analysis of the development of a software system for business metrics tracking, with a focus on practicality and usefulness for business owners. The software system can be used in various fields and industries, providing an effective tool for managing business metrics.